Multi-Omics Analysis Reveals Disturbance of Nanosecond Pulsed Electric Field in the Serum Metabolic Spectrum and Gut Microbiota - Dong, Yeping; Lu, Jiahua; Wang, Ting; Huang, Zhiliang; Chen, Xinhua; Ren, Zhigang; Hong, Liangjie; Wang, Haiyu; Yang, Dezhi; Xie, Haiyang; Zhang, Wu (Frontiers in Microbiology, 2021)
Nanosecond pulsed electric field (nsPEF) is a novel ablation technique that based on high-intensity electric voltage to achieve tumor-killing effect in the target region, and increasingly considered for treating tumours of the liver, kidneys, and other organs with rich blood supply. This study aims to observe effect of nsPFE treatment on serum metabolites and gut microbiota. The serum and fecal specimens of the pigs were collected pre-treatment and post-treatment. The gut microbiota of pigs was sequenced by Illumina Miseq platform for analyzingthe diversity and alterations of gut microbiota. Liquid chromatography-mass spectrometry (LC-MS) based metabonomic analysis and Pearson coefficient method were also used to construct the interaction system of different metabolites, metabolicpathways and flora. A total of 1477 differential metabolites from the serum were identifiedby 4 cross-comparisons of different postoperative groups with the control group. And an average of 636 OTUs per sample was detected. Correlation analysis also revealed the strong correlation between intestinal bacteria and differential metabolites. The nsPEF ablation of the liver results in a degree of liver damage that affects various metabolic pathways, mainly lipid metabolism, as well as gut microbiota. In conclusion, our study provided a good point for the safety and feasibility of applying nsPEF on liver through the integrated analysis of metabolomics and microbiomes, which is beneficial for the improvement of nsPEF in clinical use.